Merriam-Webster's Collegiate Dictionary (USA Merriam-Webster Inc., 1995)
Based on Webster's Third International Dictionary, this desk dictionary reflects the descriptive philosophy of the parent volume. The dictionary lists upwards of 150,000 entries and emphasizes contemporary pronunciation, meaning and use. This is one of the finest mid-sized dictionaries available and should be in every collection at every level
The Voice of Authority
Keywords: Languages (3GddZGJs; General -- Dictionaries; English language; Dictionaries -- English